Decentralization of Corruption and Local Public Service Delivery in Nepal - Panta, Krishna Raj (NRB Economic Review, 2016)
Lack of transparency, accountability, and existence of elite capture, ambiguity etc. will lead to misallocation and misappropriation of available resources. These phenomena contribute directly or indirectly to corruption resulting to poor efficiency and effectiveness of service delivery. These cases exist at the local level as well during the practice of decentralized service provision, leading to degrade the quality of and people’s trust on local public services. As represented by petty corruption at local level it seems to be decentralization of corruption as well in the same direction of decentralization of authorities and funds from centre to local governments. This paper tries to examine the effect of these factors on the local public service delivery in developing countries like Nepal. The study finds the existence of elite capture and corruption leading to the dissatisfaction of local people due to inferior quality of local public goods and services. Using survey data, mixed method of analysis and descriptive tools, the study examines how these maladies are affecting the local service provision through the impact on the corruption equation by the increased monopoly power of local officials along with discretion in decision making and reduced accountability. It observes the various practice of corruption existing in the local bodies and people’s perception on the corruption and local public services in the sample villages. The paper concludes that- unless and until the proper policies and actions to tackle these maladies are adopted, no one can expect for the effective and efficient decentralized service provision in order to improve the quality of life of general people.